PENGARUH IMPLEMENTASI AKUNTANSI LINGKUNGAN TERHADAP KINERJA LINGKUNGAN DAN PENGUNGKAPAN INFORMASI LINGKUNGAN SERTA DAMPAKNYA TERHADAP KINERJA KEUANGAN PERUSAHAAN - Dian Imanina Burhany (Indonesian Journal of Economics and Business, 2011)
This study examines the influence of environmental accounting implementation on environmental performance and environmental information disclosure and their impact on firm’s financial performance. Respondents are accounting department heads of 30 general mining firms participated in PROPER period 2008-2009. Primary data are collected by using questionnaires while secondary data are collected from internet publication and direct from the firms. Path analysis method is applied to test the hypotheses by using software Lisrel 8.70.The result of this study shows that: (1) environmental accounting implementation has significant and positive influence on environmental performance, (2) environmental accounting implementation and environmental performance have significant and positive influence on environmental information disclosure, both simultaneously and partially, and (3) environmental accounting implementation, environmental performance, and environmental information disclosure have significant and positive influence on financial performance simultaneously, but only environmental accounting implementation and  environmental performance have significant and positive influence on financial performance partially.